Penerapan Strategi Brain Based Learning terhadap Hasil Belajar IPA Siswa Kelas V SD Negeri 5 Banda Aceh - Suci Fitriani; Tursinawati Tursinawati; Nurmasyitah Nurmasyitah; Sulaiman Sulaiman (Pesona Dasar : Jurnal Pendidikan Dasar dan Humaniora, 2021)
The purpose of this study was to determine the application of brain based learning strategies to science learning outcomes for fifth grade students of SD Negeri 5 Banda Aceh. who are taught using Brain Based Learning and Expository learning strategies. This research is a semi-experimental research conducted at SDN 5 Meuraxa sub-district, Banda Aceh. The sample in this research is 36 students of class VB who will be used as control class and 37 class of VC class will be used as experimental class which will be conducted randomly. Data collection techniques using instruments consisting of: science learning outcomes test. The instrument used has been standardized and the validity of the test items has been obtained. Based on hypothesis testing with = 5%, it was obtained that: (1) there were differences in the science learning outcomes of students who were taught using Brain Based Learning strategies and expository learning strategies. From the results of the study, the researchers suggest that the application of Brain Based Learning strategy can be used as an alternative in improving science learning outcomes, so it can be used as input for teachers and also principals to be developed as an effective learning strategy.